'Liberal disaffection such as has not been seen in Scotland': Home Rule, Political Organisation and the Liberal Party in 1886. Issue 1 (April 2023) - Lloyd-Jones, Naomi
Abstract : The Liberal party dominated nineteenth century Scottish political life, but the Irish Home Rule crisis of 1886 inflicted damage from which it would never fully recover. This article draws on the author's study of the hundreds of constituency meetings at which the Irish question was discussed in the spring of 1886, the volume and intensity of which heightened and maintained the sense of crisis outside parliament, raised awareness of the policy locally and helped identify its supporters and opponents. These meetings are indicative of the imperative Scottish Liberals felt to discuss Home Rule and declare opinion thereon, and of the conflicting interpretations which emerged of what such opinion meant, what it was worth and who it represented. The crisis arrived at a time of intense Liberal disagreement over the purpose of party organisation and its relationship to 'Scottish opinion', and revealed both a remarkable degree of division within local party associations and a lively debating culture within the constituencies. Examining the relationship between Home Rule and party organisation prompts questions about the cohesion and coherence of 'Liberal Scotland' at both local and national levels. This article reveals the conditional character of party loyalty on Home Rule and the depth and breadth of the split in Scotland.